The research potential of new types of enterprise data based on surveys from official statistics in Germany - Joachim Wagner (Institute for the Study of Labor (IZA), 2009)
A new generation of data sets became available recently in the research data centres of the German statistical offices. These new data combine information for firms gathered in different surveys (or from other sources) that could not be analyzed jointly before. This paper offers a short description of these data, and gives examples of their use to demonstrate their research potential. Furthermore, and looking ahead to the next generation of data, it discusses an ongoing project, KombiFiD, that will for the first time offer access to linked firm level data collected by different data producing public institutions.
urn:nbn:de:101:1-2009092846
Keywords: C8; 330; Enterprise data; Germany; research data centres; Statistik der Unternehmen und Arbeitsstätten; Mikrodaten; Wirtschaftsforschung; Deutschland